The power of sovereignty : the political and ideological philosophy of Sayyid Qutb - Khatab, Sayed (Routledge studies in political Islam, 2006)
"The Power of Sovereignty attempts to understand the ideas and thoughts of Sayyid Qutb whose corpus of work and, in particular, his theory of hakimiyyah (sovereignty) is viewed as a threat to nationalistic government and peace worldwide. This book provides a detailed perspective of Sayyid Qutb's writings."--Jacket